2012
DOI: 10.1038/bmt.2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal SCT ameliorates refractory cytopenia in patients with systemic lupus erythematosus

Abstract: Our previous data have revealed that proteinuria, antinuclear antibodies and anti-dsDNA antibodies in refractory systemic lupus erythematosus (SLE) reduced after MSC infusion. This study focused on the roles of mesenchymal SCT (MSCT) in SLE patients with refractory cytopenia. Thirty-five SLE patients with refractory cytopenia were enrolled in a MSCT trial. Hematological changes of pre-and post-transplantation were evaluated. Mechanisms for MSCT effects focused on the analysis of percentage of regulatory T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…Improvement in cytopenias after MSC treatment has also been seen in mouse models of acute radiation syndrome [33,34]. In addition, MSC infusion in systemic lupus erythematosus patients with refractory cytopenias resulted in increased blood cell counts, which might have been associated with the reconstitution of regulatory T and Th17 cells [35].…”
Section: Discussionmentioning
confidence: 90%
“…Improvement in cytopenias after MSC treatment has also been seen in mouse models of acute radiation syndrome [33,34]. In addition, MSC infusion in systemic lupus erythematosus patients with refractory cytopenias resulted in increased blood cell counts, which might have been associated with the reconstitution of regulatory T and Th17 cells [35].…”
Section: Discussionmentioning
confidence: 90%
“…Initially three reports appeared in the same year; one with two patients who failed to respond to autologous bone marrow derived MSC clinically despite an increase in circulating Treg cells [16] and two other reports, both from the same centre, showing clinical improvement in 15 patients treated with allogeneic bone marrow derived MSC [17] and also in 16 similar patients who had received allogeneic umbilical derived MSC [18]. Further reports from the same centre showed improvement in four SLE patients with pulmonary haemorrhage [19] using umbilical cord derived MSC and 35 with refractory cytopenias [20] using either allogeneic bone marrow or umbilical cord MSC. Between 2012 and 2014 the same group has published 4 further SLE case series, 87 clinically heterogenoeus patients [21], 58 refractory nephritis patients [22], 40 mostly refractory nephritis patients [23] and a further 81 refractory nephritis patients [24].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 87%
“…After 3 d of culture, nonadherent cells were removed and the medium was changed twice weekly thereafter. Once 80% confluence was reached, adherent cells were replaced at a density of 10 4 cells/cm 2 for expansion (26,29).…”
Section: Human Bmmsc Isolation and Culturementioning
confidence: 99%
“…We and others have shown that lupus BMMSCs grow slowly with early signs of senescence, and exhibit some disorders in cytoskeleton and ultrastructure (23)(24)(25). In addition, accumulating evidence has indicated that allogeneic normal MSCs, rather than autologous MSC transplantation (MSCT), are more effective in treating lupus in preclinical animal studies and SLE patients (26)(27)(28)(29), which suggests that lupus MSCs have a deficiency in suppressing SLE inflammation. However, whether lupus MSCs are functionally impaired in inhibiting normal B cells remains elusive.…”
mentioning
confidence: 97%